La astronomía en el Bachillerato : diferentes enfoques - Fernández Uría, E. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this article the authors defend the introduction of Astronomy into secondary education, given the cultural and educative richness of this science. Different teaching procedures are briefly analysed, among which the use of Astronomy as a source of questions and problems of didactic value is emphasized. Different examples are offered showing the variety of possibilities than can be explored by teachers.